Impact of genetic polymorphisms of drug transporters ABCB1 and ABCG2 and regulators of xenobiotic transport and metabolism PXR and CAR on clinical efficacy of dasatinib in chronic myeloid leukemia - Madejczyk, Anna Marta; Canzian, Federico; Góra-Tybor, Joanna; Campa, Daniele; Sacha, Tomasz; Link-Lenczowska, Dorota; Florek, Izabela; Prejzner, Witold; Całbecka, M.; Rymko, M.; Dudziński, M.; Orzechowska, Magdalena Julita; et al. (Frontiers in Oncology, 2022)
Introduction Functional single-nucleotide polymorphisms (SNPs) in genes regulating cellular uptake, elimination, and metabolism of xenobiotics may potentially influence the outcome of chronic myeloid leukemia (CML) patients treated with BCR-ABL1 tyrosine kinase inhibitors (TKI). Dasatinib, a second-generation TKI, is a substrate of the ABC-superfamily xenobiotic transporters ABCB1 (MDR1, Pg-P) and ABCG2 (BCRP). Pregnane X receptor (PXR, NR1I2) and constitutive androstane receptor (CAR, NR1I3) are involved in the control of expression of ABCB1 and ABCG2. Aim of the study In this study, we assessed the impact of inherited variants in ABCB1, ABCG2, PXR, and CAR genes on dasatinib efficacy and toxicity in CML. Materials and methods Sixty-one tagging SNPs in ABCB1, ABCG2, PXR, and CAR genes were analyzed by real-time quantitative PCR with specific probes in 86 CML patients who failed imatinib therapy. Results We found the associations between SNPs rs7787082 (ABCB1, OR = 0.2; 95% CI = 0.06-0.66, p = 0.008), rs12505410 (ABCG2, OR = 3.82; 95% CI = 1.38-10.55; p = 0.010), and rs3114018 (ABCG2, OR = 0.24; 95% CI = 0.08-0.71; p = 0.010) and the probability of achieving CCyR. Furthermore, progression-free survival (PFS) was significantly influenced by SNPs rs3732357 (HR = 0.2, 95% CI = 0.26-0.70; p = 0.001), rs3732360 (HR = 0.59; 95% CI = 0.38-0.93; p = 0.020), rs11917714 (HR = 0.58; 95% CI = 0.36-0.92; p = 0.020), and rs3732359 (HR = 0.57; 95% CI = 0.36-0.91; p = 0.024) in PXR; rs2307418 (HR = 2.02; 95% CI = 1.19-3.43; p = 0.048) in CAR; and rs2235023 (HR = 2.49; 95% CI = 1.13-5.50; p = 0.011) and rs22114102 (HR = 1.90; 95% CI = 1.00-3.63; p = 0.028) in ABCB1. Moreover, overall survival (OS) was impacted by rs3842 (HR = 1.84; 95% CI = 1.01-3.33; p = 0.012) and rs2235023 (HR = 2.28; 95% CI = 1.03 = 5.02; p = 0.027) in ABCB1, rs11265571 (HR = 1.59; 95% CI = 0.82-3.08; p = 0.037) and rs2307418 (HR = 73.68; 95% CI = 4.47-1215.31; p = 0.003) in CAR, and rs3732360 (HR = 0.64; 95% CI = 0.40 = 1.04; p = 0.049) in PXR. Taking into account the influence of the tested SNPs on treatment toxicity, we found a significant relationship between allele G of polymorphism in the ABCB1 rs7787082 (OR = 4.46; 95% CI = 1.38-14.39 p = 0.012) and hematological complications assuming the codominant gene inheritance model as well as a significant correlation between the presence of minor allele (G) of SNP rs2725256 in the ABCG2 gene (OR = 4.71; 95% CI = 1.20-18.47; p = 0.026) and the occurrence of non-hematological complications assuming a recessive gene inheritance model. Conclusion Our data suggest that inherited variants in the genes encoding for proteins involved in the transport of xenobiotics may modify the toxicity and efficacy of dasatinib therapy in CML patients.